DISTRIBUTION OF Salmonella SEROTYPE FROM SLAUGHTERHOUSE (RPH) AND CHICKEN ABATTOIR (TPA) IN BOGOR - Widodo Suwito (Widyariset, 2011)
Salmonella serotypes are found at the slaughterhouse (RPH) and chicken abattoir (TPA). The aim of these re-search was to determination the distribution of Salmonella serotypes from the RPH and TPA. Total of 267 samples were to collected from RPH and TPA in Bogor. These samples consisted of 98 carcass, 16 ﬂ oors swab, 8 knife swab, 1 table swab, 13 tub water, 4 waste water, 37 mesenteric glands, 50 caecum, 38 faeces, and 2 chicken nuggets were analyzed for Sallmonella contents using biochemical reaction and serology. The research showed that RPH and TPA in Bogor were contaminated by Salmonella enteritidis, Salmonella schwarzengrund, Salmonella weltevreden,and Salmonella typhimurium. The distribution Salmonella serotype from RPH and TPA in Bogor occurred in the caecum, mesentery glands and carcass.